A performatividade da Teoria da Agência nos órgãos de controle do executivo: o caso da controladoria do Estado de São Paulo - Waack, Herbert Annes Dias (Universidade Federal de São Carlos, 2025)
This research analyzes how agency theory influenced the institutionalization process of comptroller offices in the public sector of the state of São Paulo. Based on the performativity approach and the assumptions of actor-network theory, we aim to demonstrate that agency theory played a decisive role in the diffusion of public comptroller offices in Brazil. The research method employed was the mapping of controversies, through which we charted both human and non-human actors involved in this institutionalization process, from its historical origins to the recent establishment of the General Comptroller Office of the State of São Paulo. The study included qualitative data analysis, examination of documents, published news, and legislative discussions available on the World Wide Web, as well as a bibliographic review of analyses published in scientific texts. Comptroller offices play a key role in constructing public governance that mirrors the corporate governance model of publicly traded companies. Agency theory has performed in public management by influencing the consolidation of comptroller offices as instruments that replicate the principles of corporate governance adopted by these companies. The application of these concepts has promoted greater transparency, accountability, and rigorous control of public resources. Through mechanisms such as internal audits and performance reports, comptroller offices have established public governance that reflects corporate models, emphasizing integrity, responsibility, and efficiency in administration. This approach has created a supervisory structure that reinforces the commitment to responsible resource use and strengthens trust between public agents and society.
The performativity of Agency Theory in executive branch oversight institutions: the case of the São Paulo State comptroller general’s office
Keywords: Controladoria; Teoria da Agência; Performatividade; Controllership; Agency Theory; Performativity; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS